Acute hemodynamic changes and long term prognostic impact of pulmonary hypertension in patients undergoing percutaneous mitral valve edge to edge repair. (25th November 2020) - Koell, B; Ludwig, S; Bhadra, O; Gossling, A; Schofer, N; Schirmer, J; Conradi, L; Reichenspurner, H; Blankenberg, S; Lubos, E; Kalbacher, D
Abstract: Background: Pulmonary hypertension (PH) due to left heart disease is the most common form of PH. Published literature suggests increased perisurgical mortality in patients undergoing surgical repair in the setting of preexisting PH. The data on the impact of preexisting PH on clinical outcomes after percutaneous Mitral Valve Edge-to-Edge Repair (pMVR) is limited to observational studies and rely mostly on echocardiographic data. Purpose: The aim of the current study is to evaluate the influence of preexisting PH in patients undergoing pMVR analyzing periprocedural invasive right heart catheterization data. Methods: Between September 2008 and July 2018, a total of 911 patients with moderate-to-severe or severe mitral regurgitation (MR) underwent pMVR at our center. This analysis includes 331 patients with a complete data set for pre- and postprocedural right heart catheterization and echocardiographic assessment as well as available follow-up information after the implantation. Patients are divided according to the etiology of PH. The combined primary endpoint consists of all-cause mortality and rehospitalization for heart failure. Furthermore, a sub-analysis is performed for all patients with preexisting post-capillary PH. Patients with post-capillary PH are divided into two groups based on a postprocedural decrease of pulmonary artery wedge pressure (mPAWP) below the threshold of 15mmHg. Univariate and multivariate Cox regression analyses are performed to assess the influence on long-term outcome. Results: Of all 331 patients (57.7% [n= 191] male) undergoing pMVR, 195 (62.1%) had functional MR. Median ejection fraction was 40.5% (29.3, 54.0). Patients were followed-up for a maximum of 4.41 years and the median follow-up time was 1.98 years. Preexisting PH (mean pulmonary artery pressure ≥25 mmHg) was found in 236 (71.1%) patients: 49 patients had pre-capillary PH (≤15 mmHg), 187 had post-capillary PH (pcPH; n=183; mPAWP >15 mmHg). In Kaplan-Meier analysis, no statistically significant difference could be found in overall mortality in patients without or with PH, irrespective of etiology (p=0.43). However, in patients suffering from post-capillary PH, patients with a postprocedural reduction of mPAWP below the threshold of 15mmHg showed a significantly lower risk for overall long-term mortality compared to patients without a relevant mPAWP reduction (p=0.018). Multivariate analysis revealed acute postprocedural decrease of mPAWP below 15mmHg in patients with post-capillary PH to have a significant influence on mortality (HR 2.81 [1.35, 5.86]; p=0.006; Figure 1). Conclusion: In contrast to previously published findings, the present results were not able to show a significant impact of PH, disregarding its etiology, on outcome. Nevertheless, a postprocedural decrease of mPAWP below 15mmHg in patients with post-capillary PH is associated with a favorable outcome. Funding Acknowledgement: Type of funding source: None